Case report of a child with influenza and fatal community-associated methicillin-resistant Staphylococcus aureus sepsis - Boettger, Bruno Cruz; Teles Rezende, Thais Freitas; Teixeira, Nathalia Bibiana [UNESP]; Campos Pignatari, Antonio Carlos; Veiga Kiffer, Carlos Roberto (Soc Brasileira Medicina Tropical, 2020)
In the present study, we report the incidence of septic shock syndrome associated with methicillin-resistant Staphylococcus aureus in a child who initially presented influenza-like illness and developed septic shock shortly after 48 h of hospitalization, and eventually died within a few hours of the onset of sepsis. S. aureus isolated from the blood culture was characterized as the community-associated strain carrying the staphylococcal cassette chromosome mec (SCCmec) type IV element. Therefore, it is important to better understand the community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) infections and their potential association with influenza for early diagnosis and successful treatment of this fatal disease.
Keywords: Staphylococcus aureus; Methicillin resistance; Influenza virus